Formation and hydrogen storage behavior of nanostructured Mg2FeH6 in a compressed 2MgH2–Fe composite. (21st August 2020) - Khan, Darvaish; Panda, Subrata; Ma, Zhewen; Ding, Wenjiang; Zou, Jianxin
Abstract: The present study focuses on enhancing the yield of Mg2 FeH6 and its hydrogen storage performances through a novel high-pressure compression approach. For which, MgH2 and Fe powders are first mechanically milled in a molar ratio of 2:1 and subsequently compressed to a cylindrical pellet. Due to the compression, the yield of Mg2 FeH6 in the compressed 2MgH2 –Fe pellet (90%) has been increased by 24% as compared to the reference ball-milled powder (66%). The thermodynamic destabilization of Mg2 FeH6 in the pelletized sample is observed through measuring the pressure-composition isotherms, resulting in the reduced ab/desorption enthalpy for the pellet sample (−68.34 and 75.61 kJ/mol H2, respectively). The hydrogen uptake and release kinetics of Mg2 FeH6 is remarkably fast, and it can store/release about 5 wt% H in less than 2.5 min at 400 °C. The faster hydrogen ab/desorption kinetics corresponds to the lower activation energies (36 and 95 kJ/mol H2, respectively). The excellent yield of Mg2 FeH6 and its improved hydrogen storage properties for the compressed pellet are primarily attributed to the microstructural modifications upon high-pressure compression, and also the obtained results for Mg2 FeH6 ternary hydride are linked to the literature data based on theoretical calculations. Highlights: MgH2 and Fe powders mixture was ball milled and compressed into pellet form. The yield of Mg2 FeH6 in the compact pellet was 24% more than the ball-milled powder. In 2MgH2 –Fe compact, Fe nanoparticles were less agglomerated during H-cycling. Excellent thermodynamic properties of Mg2 FeH6 led to the reduced enthalpies. H-ab/desorption of Mg2 FeH6 was very fast with lower ab/desorption activation energies.